G75(P) Optimal duration of parenteral antibiotic therapy in children with uncomplicated acute haematogenous osteomyelitis: A review of local practice and impact on patient experience. (27th April 2016) - Mitchell, F; Halbert, J; Gite, A
Abstract : Aims: The evidence-base for the optimal duration of parenteral antibiotics in paediatric uncomplicated acute haematogenous osteomyelitis (PUAHO) before switching to oral antibiotics is limited. Here we review current practice at a district general hospital (UK); patient/carer experience; and recommendations by regional experts. Methods: Patient medical notes, laboratory and radiological results were reviewed for all children <16 years with a diagnosis of osteomyelitis at a district general hospital in the UK between 1 st July 2013 and 1 st August 2014. Demographic and clinical details were recorded in a secure anonymous database. A literature review and email survey of regional paediatric microbiology, infectious disease and orthopaedic experts was undertaken. Semi-structured telephone interviews with carers was conducted and transcripts analysed using a qualitative framework. Results: 5 patients were diagnosed with osteomyelitis. 1 was secondary to a supracondylar fracture and 1 had septic arthritis and so were excluded from clinical analysis but included in the telephone survey. The duration of parenteral antibiotics varied from 3–6 weeks and continued for >14 days after normalisation of inflammatory markers and resolution of clinical signs. Regional experts confirmed "there is considerable variability in practice and limited evidence when to switch antibiotics" (range of minimum duration of parenteral antibiotics 2–6 weeks). They highlighted concerns regarding oral antibiotic compliance and that some carers are not comfortable switching early especially if they believe their child has a serious infection. From the telephone survey carers reported they found "multiple opinions for the duration of treatment confusing." Multiple cannulas (>10) and trips to the hospital caused significant anxiety and disruption for family and school life. Carers would find oral antibiotics preferable "so long as they work, " although one carer found the administration of them more challenging. Conclusions: There is currently no consensus and considerable variation in regional practice for the management of PUAHO. Unnecessary prolonged courses of parenteral antibiotics can have adverse financial and patient/carer experience implications. This study highlights the pressing need for robust evidence regarding the optimal duration of parenteral antibiotic therapy in PUAHO. The UK multicentre DINOSAUR study on the management of paediatric osteomyelitis is likely to provide further evidence.